2011
DOI: 10.3386/w16664
|View full text |Cite
|
Sign up to set email alerts
|

Long-run Impacts of School Desegregation & School Quality on Adult Attainments

Abstract: This paper investigates the long-run impacts of court-ordered school desegregation on an array of adult socioeconomic and health outcomes. The study analyzes the life trajectories of children born between 1945 and 1968, and followed through 2013, using the Panel Study of Income Dynamics (PSID). The PSID data are linked with multiple data sources that describe the neighborhood attributes, school quality resources, and coincident policies that prevailed at the time these children were growing up. I exploit quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
210
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(214 citation statements)
references
References 13 publications
2
210
1
1
Order By: Relevance
“…It also includes work on the effects of K-12 desegregation policy on segregation levels (Reber 2005), school district finances (Reber 2011), housing prices (Boustan 2012), residential and school choices (Baum-Snow and Lutz 2011), educational outcomes (Guryan 2004;Reber 2010;Johnson 2011), economic outcomes (Johnson 2011), 4 health (Johnson 2010(Johnson , 2011, and crime (Weiner, Lutz, and Ludwig 2009;Johnson 2011). 1 Clotfelter, Vigdor, and Ladd (2006);Lutz (2011);and Reardon et al (2012) have studied whether there is "resegregation" now that desegregation plans are being lifted.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It also includes work on the effects of K-12 desegregation policy on segregation levels (Reber 2005), school district finances (Reber 2011), housing prices (Boustan 2012), residential and school choices (Baum-Snow and Lutz 2011), educational outcomes (Guryan 2004;Reber 2010;Johnson 2011), economic outcomes (Johnson 2011), 4 health (Johnson 2010(Johnson , 2011, and crime (Weiner, Lutz, and Ludwig 2009;Johnson 2011). 1 Clotfelter, Vigdor, and Ladd (2006);Lutz (2011);and Reardon et al (2012) have studied whether there is "resegregation" now that desegregation plans are being lifted.…”
Section: Previous Researchmentioning
confidence: 99%
“…Although little is known about racial segregation at the college level, research on K-12 schools has found negative effects of racial segregation on students and has found positive effects of desegregation plans (Guryan 2004;Johnson 2010Johnson , 2011Reber 2010;Weiner, Lutz, and Ludwig 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An individual's earnings are a function of his health stock h and his education level e, where education also depends upon the health stock. Formally, y = y(e, h) = y(e(h(I 1 , I 2 )), h(I 1 , I 2 )), where y represents earnings 7 The restricted version of the Panel Study of Income Dynamics (PSID) is the best currently available dataset that gives information on location and date of birth linked to long-run earnings (Johnson and Schoeni, 2007;Hoynes, Schanzenbach, and Almond, 2012;Johnson, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…MacInnis (2009) finds that primary and secondary school quality significantly increases cognitive functioning in old age. Johnson (2010) demonstrates that the increases in school quality following school desegregation improved adult self-reported health status for blacks.…”
Section: Introductionmentioning
confidence: 99%